Comparison of Efficacy of Duloxetine Versus Amitriptyline in Fibromyalgia Patients - Saira Tahir; Obaid ur Rehman; Aliena Badshah; Durkho Atif; Muhammad Muddasser Khan Panezai; Alam Zeb (Journal of Aziz Fatimah Medical and Dental College)
ABSTRACT Objective: To compare the outcomes of Duloxetine and Amitriptyline therapy in fibromyalgia patients regarding change in Symptom Severity Scale (SSS) score and Widespread Pain Index (WPI) from baseline after three months of treatment. Methodology: This quasi-experimental study was done in the Department of Rheumatology, Pakistan Institute of Medical Sciences, Islamabad, from November 2022 to April 2023. One hundred fifty-six fibromyalgia patients of either gender between the ages of 25-70 years were included in the study. They were erratically assigned into two groups. Group A patients were given Duloxetine, while group B patients were given Amitriptyline for 12 weeks with main outcome of change in WPI and SSS scores three months after the therapy. Results: There were 2.6% (n=2/78) males and 97.4% (n=76/78) females in group A and 1.3% (n=1/78) males and 98.7% (n=77/78) females in group B (P=0.560). At baseline, the mean WPI score in group A was 15.8 ± 1.3 SD, and it was 16.1 ± 1.4 SD in group B (P=0.286), and the mean SSS score was 6.6 ± 1.6 SD in group A, and it was 6.8 ± 1.5 SD in group B (P=0.467). At 12 weeks, the mean WPI score in group A was 11.2 ± 2.2 SD, and it was 8.9 ± 3.1 SD in group B (P=0.001), and the mean SSS score was 4.5 ± 1.7 SD in group A, and it was 3.6 ± 1.3 SD in group B (P=0.001). Conclusions: Outcomes were better with Amitriptyline compared to those patients taking Duloxetine in diagnosed cases of fibromyalgia.